2021
DOI: 10.1002/pon.5641
|View full text |Cite
|
Sign up to set email alerts
|

Use of psychotropic drugs among older patients with bladder cancer in the United States

Abstract: Objective Older patients diagnosed with cancer are at increased risk of physical and emotional distress; however, prescription utilization patterns largely remain to be elucidated. Our objective was to comprehensively assess prescription patterns and predictors in older patients with bladder cancer. Methods A total of 10,516 older patients diagnosed with clinical stage T1–T4a, N0, M0 bladder urothelial carcinoma from 1 January 2008 to 31 December 2012 from the Surveillance, Epidemiology, and End Results (SEER)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 48 publications
(66 reference statements)
0
4
0
Order By: Relevance
“…As the authors note, this cannot be determined from the study because of the inability to account for stage and prior treatment. However, among patients with bladder cancer, higher prescription rates were observed with higher stage bladder cancer (with the exception of stage IV disease) 18 …”
mentioning
confidence: 95%
See 3 more Smart Citations
“…As the authors note, this cannot be determined from the study because of the inability to account for stage and prior treatment. However, among patients with bladder cancer, higher prescription rates were observed with higher stage bladder cancer (with the exception of stage IV disease) 18 …”
mentioning
confidence: 95%
“…Prior work examining psychiatric resource use as a surrogate of disease severity, showed that increasing level of precancer diagnosis psychiatric resource use (none vs outpatient vs emergency room) was associated with worse cancer‐specific and overall survival 5 . A recent study by Jazzar et al 18 evaluated prescription patterns in patients with bladder cancer using Surveillance, Epidemiology, and End Results data with and without existing psychiatric history, finding that 53% of patients were prescribed a psychotropic drug within 2 years of bladder diagnosis. Those with a history of psychiatric disease were more likely to have a psychotropic prescription following their diagnosis, indicating that clinicians should be aware of this history and its presumable increased risk of mental health diagnosis or exacerbation during and after cancer diagnosis.…”
mentioning
confidence: 99%
See 2 more Smart Citations